Synchronization of circular restricted three body problem with lorenz hyper chaotic system using a robust adaptive sliding mode controller. Issue 6 (26th July 2013) - Khan, Ayub; Shahzad, Mohammad
<x xml:space="preserve">Abstract</x> In this computational study, we synchronize the Circular Restricted Three Body Problem (CRTBP) with Lorenz Hyper Chaotic System (LHCS) using a Robust Adaptive Sliding Mode Controller (RASMC) together with uncertainties, external disturbances and fully unknown parameters. A simple suitable sliding surface, which includes synchronization errors, is constructed and appropriate update laws are used to tackle the uncertainties, external disturbances and unknown parameters. All simulations to achieve the synchronization for the implemented technique for the two non‐identical systems under consideration are being done using Mathematica. © 2013 Wiley Periodicals, Inc. Complexity 18: 58‐64, 2013